Surgery and trauma care providers' perception of the impact of dual‐practice employment on quality of care provided in an Andean country. Issue 6 (2nd March 2017) - LaGrone, L. N.; Isquith‐Dicker, L. N.; Huaman Egoavil, E.; Herrera‐Matta, J. J.; Fuhs, A. K.; Ortega Checa, D.; Revoredo, F.; Rodriguez Castro, M. J. A.; Mock, C. N.
Abstract: Background: Dual‐practice, simultaneous employment by healthcare workers in the public and private sectors is pervasive worldwide. Although an estimated 30 per cent of the global burden of disease is surgical, the implications of dual practice on surgical care are not well understood. Methods: Anonymous in‐depth individual interviews on trauma quality improvement practices were conducted with healthcare providers who participate in the care of the injured at ten large hospitals in Peru's capital city, Lima. A grounded theory approach to qualitative data analysis was employed to identify salient themes. Results: Fifty interviews were conducted. A group of themes that emerged related to the perceived negative and positive impacts of dual practice on the quality of surgical care. Participants asserted that the majority of physicians in Lima working in the public sector also worked in the private sector. Dual practice has negative impacts on physicians' time, quality of care in the public sector, and surgical education. Dual practice positively affects patient care by allowing physicians to acquire management and quality improvement skills, and providing incentives for research and academic productivity. In addition, dual practice provides opportunities for clinical innovations and raises the economic status of the physician. Conclusion: Surgeons in Peru report that dual practice influences patient care negatively by creating time and human resource conflicts. Participants assert that these conflicts widen the gap in quality of care between rich and poor. This practice warrants redirection through national‐level regulation of physician schedules and reorganization of public investment in health via physician remuneration. Abstract : Unfocused and fatigued